KNOWLEDGE, ATTITUDE AND PRACTICES OF HEALTHCARE PROVIDERS TOWARDS DEEP VEIN THROMBOSIS PROPHYLAXIS IN FIVE TEACHING HOSPITALS OF RAWALPINDI - Bhatti, Ahsin M; Ahsin, Sadia; Salim, Babur; Mansoor, Junaid (Journal of Ayub Medical College Abbottabad, 2012)
Background: Prophylaxis of deep vein thrombosis (DVT) is underutilised in Pakistan. This crosssectional survey was designed to evaluate knowledge, attitude and practices of healthcare providers towards DVT prophylaxis in teaching hospitals in and around Rawalpindi. Methods: Knowledge, attitude and practices was assessed by a 12-item questionnaire filled-in by healthcare providers in five teaching hospitals. Eleven out of 12 questions were multiple-choice type and one was open ended. Results: One hundred-sixty-nine, out of 200 questionnaires were returned and were analysed. Total 43.2% of the respondents were house-officers. Although 98.8% agreed that DVT prophylaxis is clinically important, but 39.4% actually prescribed it themselves. Out of these, only 10.3% respondents did it routinely. Low molecular weight heparin (LMWH) was the preferred prophylaxis used (36.7%). Most of the respondents underestimated the prevalence and consequences of DVT in hospitalised patients. Conclusion: Knowledge and practices of healthcare providers about DVT prophylaxis in hospitalised patients is less than ideal. Hospitals need to develop their own guidelines for DVT prophylaxis. Keywords: Knowledge, Attitude, Practices, DVT Prophylaxis, Pakistan